2008
DOI: 10.1002/ptr.2513
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antidiabetic activities of five medicinal herbs used in Chinese medicinal formulae

Abstract: Fructus Corni, Fructus Schisandrae Chinensis, Poria, Rhizoma Alismatis and Rhizoma Dioscoreae are commonly used in traditional Chinese medicine for diabetes treatment. They are also the component herbs of an antidiabetic foot ulcer formula with demonstrated clinical efficacy. Although some of these herbal extracts were previously shown to possess in vivo antidiabetic effects (i.e. lowering blood glucose levels), the underlying mechanisms remain elusive. The objective of this study is to investigate the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…3T3-L1 adipocyte differentiation, triglyceride accumulation and PPAR-agonist activity PPAR-␥ agonists are insulin sensitizers that increase triacylglycerol storage in adipose tissues by increasing insulin-stimulated glucose uptake (Lau et al, 2008). FS-60 dose-dependently increased differentiation and triglyceride accumulation in comparison to the vehicle-treated control during treatment for 10 days in 3T3-L1 adipocytes ( Fig.…”
Section: Insulin-stimulated Glucose Uptake In 3t3-l1 Adipocytesmentioning
confidence: 96%
See 1 more Smart Citation
“…3T3-L1 adipocyte differentiation, triglyceride accumulation and PPAR-agonist activity PPAR-␥ agonists are insulin sensitizers that increase triacylglycerol storage in adipose tissues by increasing insulin-stimulated glucose uptake (Lau et al, 2008). FS-60 dose-dependently increased differentiation and triglyceride accumulation in comparison to the vehicle-treated control during treatment for 10 days in 3T3-L1 adipocytes ( Fig.…”
Section: Insulin-stimulated Glucose Uptake In 3t3-l1 Adipocytesmentioning
confidence: 96%
“…Baillon, is traditionally used as a tonic, sedative and anti-diabetic agent in Asia (Huang et al, 2007;Lau et al, 2008). At the beginning of the 1970s, researchers reported that Fructus Schisandrae is effective for treating viral and chemical hepatitis, lowering elevated serum glutamate pyruvate transaminase levels, and for increasing hepatic glycogen accumulation and decreasing hepatic triglycerides.…”
Section: Introductionmentioning
confidence: 99%
“…Corni fructus is commonly used in traditional Oriental medicine for treatment of diabetes and diabetic foot ulcer. 37 However, no anti-aging properties or effects on collagen synthesis have been reported for Corni fructus or Torilus fructus. The present study is the first long-term randomized controlled trial exploring the beneficial effects of red ginseng on photoaged human skin.…”
Section: Figmentioning
confidence: 99%
“…In grapes, grape pomace was shown to reduce fasting plasma glucose, insulin and triglyceride levels in growing Sprague-Dawley rats [5]. As another blood glucose controller, omija ( Schisandra chinensis Baillon), a traditional Chinese alternative medicine, has been used as an anti-diabetic agent in Asia [6]. …”
Section: Introductionmentioning
confidence: 99%